ANALISIS CITRA ORGANISASI, KUALITAS JASA PENDIDIKAN, DAN KEPUASAN MAHASISWA BERPENGARUH TERHADAP LOYALITAS MAHASISWA - Harudin Lagio (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2012)
The results of statistical analyzes that have been conducted, it appears that hasit F test showed that Fhitug = 37.498> from F table = 1.65. This suggests that together the independent variables have a significant effect on the dependent variable. This means that the image of the organization variable (X1), the quality of education services (X2), student satisfaction (X3), simultaneously exerting influence on the formation of student loyalty Untika Luwuk Banggai. Results Adjasted R square = 0.678 which is an index of determination stated percentage of approximately 67.8% Luwuk Untika student loyalty formation is explained by three variables, while the remaining 32.2% is explained by other causes that are not a study variable.